2007
DOI: 10.1038/sj.bjp.0707383
|View full text |Cite
|
Sign up to set email alerts
|

1‐Methylnicotinamide (MNA), a primary metabolite of nicotinamide, exerts anti‐thrombotic activity mediated by a cyclooxygenase‐2/prostacyclin pathway

Abstract: Background and purpose: 1-methylnicotinamide (MNA) has been considered to be an inactive metabolite of nicotinamide. Here we assessed the anti-thrombotic activity of MNA in vivo. Experimental approach: Antithrombotic action of MNA was studied in normotensive rats with extracorporeal thrombus formation (thrombolysis), in renovascular hypertensive rats with intraarterial thrombus formation (arterial thrombosis) and in a venous thrombosis model in rats (venous thrombosis). Key results: MNA (3-100 mg kg À1 ) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
156
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(166 citation statements)
references
References 36 publications
(35 reference statements)
6
156
0
Order By: Relevance
“…These agents can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong, et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase, glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska, et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki, et al, 2007, Chong, et al, 2002d, Hara, et al, 2007, Ieraci and Herrera, 2006.Throughout the body, cell survival and lifespan is tied to the presence of oxidative stress and the subsequent induction of apoptotic cell injury , De Felice, et al, 2007, Lin and Maiese, 2001). It has recently been shown that genes involved in the apoptotic process are replicated early during processes that involve cell replication and transcription, suggesting a much broader role for these genes than originally anticipated (Cohen, et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These agents can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong, et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase, glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska, et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki, et al, 2007, Chong, et al, 2002d, Hara, et al, 2007, Ieraci and Herrera, 2006.Throughout the body, cell survival and lifespan is tied to the presence of oxidative stress and the subsequent induction of apoptotic cell injury , De Felice, et al, 2007, Lin and Maiese, 2001). It has recently been shown that genes involved in the apoptotic process are replicated early during processes that involve cell replication and transcription, suggesting a much broader role for these genes than originally anticipated (Cohen, et al, 2007).…”
mentioning
confidence: 99%
“…These agents can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong, et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase, glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska, et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki, et al, 2007, Chong, et al, 2002d, Hara, et al, 2007, Ieraci and Herrera, 2006.…”
mentioning
confidence: 99%
“…Potentially relevant to diabetic patients with renal failure, nicotinamide also has been shown to reduce intestinal absorption of phosphate and prevent the development of hyperphosphatemia and progressive renal dysfunction [81]. In animal and cell culture studies, nicotinamide also can maintain normal fasting blood glucose in animals with streptozotocin-induced diabetes [82,83], reduce peripheral nerve injury during elevated glucose [84], lead to the remission of type 1 DM in mice with acetyl-l-carnitine [85], and can inhibit oxidative stress pathways that lead to apoptosis [63, [86][87][88][89].…”
Section: Innovative Strategies For Neurovascular Protection During Dmmentioning
confidence: 99%
“…Recently, we suggested that MNA formed in the liver by nicotinamide N-methyltrasferase can be an endogenous activator of the COX-2/PGI 2 pathway and may play an important regulatory role in limiting thrombosis and inflammatory processes in the cardiovascular system [10]. The formation and progression of atherosclerotic plaques are driven by vascular inflammation and thrombosis, and both of these processes may be associated with changes in NNMTderived MNA formation.…”
Section: Introductionmentioning
confidence: 99%
“…NA is a water-soluble vitamin essential for energy supply, cell viability, and resistance to stress or injury [28]. Moreover, it has recently become apparent that MNA, long considered an inactive metabolite of NA, possess anti-thrombotic [10], antiinflammatory [8], gastroprotective [9], and vasoprotective [5] properties.…”
Section: Introductionmentioning
confidence: 99%